Spatial co-occurrence patterns of benthic microbial assemblage in response to trace metals in the Atacama Desert Coastline - Zárate, Ana; Molina, Verónica; Valdés, Jorge; Icaza, Gonzalo; Vega, Sue Ellen; Castillo, Alexis; Ugalde, Juan A.; Dorador, Cristina (Frontiers in Microbiology, 2023)
Taxonomic and functional microbial communities may respond differently to anthropogenic coastal impacts, but ecological quality monitoring assessments using environmental DNA and RNA (eDNA/eRNA) in response to pollution are poorly understood. In the present study, we investigated the utility of the co-occurrence network approach’s to comprehensively explore both structure and potential functions of benthic marine microbial communities and their responses to Cu and Fe fractioning from two sediment deposition coastal zones of northern Chile via 16S rRNA gene metabarcoding. The results revealed substantial differences in the microbial communities, with the predominance of two distinct module hubs based on study zone. This indicates that habitat influences microbial co-occurrence networks. Indeed, the discriminant analysis allowed us to identify keystone taxa with significant differences in eDNA and eRNA comparison between sampled zones, revealing that Beggiatoaceae, Carnobacteriaceae, and Nitrosococcaceae were the primary representatives from Off Loa, whereas Enterobacteriaceae, Corynebacteriaceae, Latescibacteraceae, and Clostridiaceae were the families responsible for the observed changes in Mejillones Bay. The quantitative evidence from the multivariate analyses supports that the benthic microbial assemblages’ features were linked to specific environments associated with Cu and Fe fractions, mainly in the Bay. Furthermore, the predicted functional microbial structure suggested that transporters and DNA repair allow the communities to respond to metals and endure the interacting variable environmental factors like dissolved oxygen, temperature, and salinity. Moreover, some active taxa recovered are associated with anthropogenic impact, potentially harboring antibiotic resistance and other threats in the coastal zone. Overall, the method of scoping eRNA in parallel with eDNA applied here has the capacity to significantly enhance the spatial and functional understanding of real-time microbial assemblages and, in turn, would have the potential to increase the acuity of biomonitoring programs key to responding to immediate management needs for the marine environment.